DETERMINAN KEPATUHAN WAJIB PAJAK UMKM GEN-Z DI PROVINSI BANTEN - Febriantika, Devi; Widayati, Neneng; Fauzi, Fauzi; Mulatsih, Srie Nuning; Saepuloh, Dadang (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2025)
The low presence of MSME taxpayers, especially from Generation Z in Banten Province, is an important concern in efforts to increase tax revenue. Digital transformation and tax awareness are important factors in encouraging tax participation among young entrepreneurs. This study aims to examine the effect of tax digitalization, tax understanding, tax morality, and financial conditions on MSME taxpayer compliance, as well as the role of financial conditions as a moderating variable. The study was conducted quantitatively with the SEM-PLS approach and involved 100 MSME respondents from Generation Z. The results show that tax understanding and financial conditions have a significant effect on MSME taxpayer compliance, while digitalization and morality have not shown a significant effect. The three independent variables are simultaneously able to explain variations in MSME taxpayer compliance. However, financial conditions have not been shown to significantly moderate the relationship between variables. This finding has implications for the educational aspect of technology utilization, as well as the formation of moral awareness being important for building MSME tax compliance based on the younger generation in the digital era. Recommendations for the Banten Directorate General of Taxes to improve digital tax education that is in accordance with the character of Generation Z. Fiscal literacy needs to be strengthened with a technological and social approach. Further researchers can examine the psychological and cultural factors that influence the existence of taxes.